PENGGUNAAN METODE ROLE PLAYING UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN SISWA KELAS IV MIN I METRO PUSAT TAHUN AJARAN - rosada rosada (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2016)
This research was aimed at finding out the description of using role playing methode to increase the students’ result and activity in Pendidikan Kewarganegaraan lesson at the IV grader of MIN I METRO PUSAT in the academic year of 2012/2013. This research was an action class research design. The population of this research was the IV grader of MIN I METRO PUSAT in the academic year of 2012/2013.which consist of 23 students’ that are devided onto 16 male students and 7 female students. The students activity average at siklus I is 72,24% and at siklus II is 83,09%. While the students learning result in siklus I is 69,91 with the succesful precentage is 56,5% and at siklus II is 74,34 with the succesful precentage 86,9%. Based on the result of the study, the researcher state that the use of Role Playing methode is recomended for teaching Pendidikan Kewarganegaraan lesson to increase the students’ result and activity in the class. So this lesson can be an interested lesson for the students. Key Word: Role Playing, Activity and Learning Result, Pendidikan Kewarganegaraan.